Efeito da temperatura e do tempo de sinterização nas propriedades mecânicas e termomêcanicas de cerâmicas refrátarias fabricadas com cinza da casca de arroz - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The growing demand for the reuse of industrial and agro-industrial residues in order to increase an economic potential and reduce environmental impact has driven the development of research to use rice husk ash. Recent researches have added this residue to improve the mechanical and thermomechanical properties of refractory ceramic materials, with an added improvement in properties such as resistance to compressive strength. However, a reduction in thermal shock resistance was observed, an important property for refractory ceramic materials. In this context it is possible to use a clay with a higher content of alumina to form mullite, a compound that has good mechanical and thermal properties. The main objective of this work is to study the effect of the final sintering temperature and permanent time on the mechanical and thermomechanical properties of refractory ceramic materials made with aluminous clay and rice husk ash. Mixtures were prepared with 80% aluminous clay and 20% rice husk ash. The cream was pressed at 42.5 MPa, dried and sintered at 1000°C, 1100°C or 1200°C in times of 1h or 3h. The tests of porosity, flexural strength at three points, compressive strength, thermal shock and X-Ray Diffraction were performed. The increase in firing time and temperature resulted in decreased porosity, increased flexural strength at three points, with the exception of the sample sintered at 1200°C for 3h, increase in compressive strength until the sample sintered at 1100°C for 3h and increase in the number of cycles of the thermal shock test. The predominant crystalline phases were corundum, mullite and the quartz found at temperature of 1000oC had its crystal structure altered and turned into cristobalite from 1100oC. Keywords: rice husk ash; refractory ceramic materials; sintering; thermal shock resistence.
Keywords: Engenharia mecânica; Arroz; Cerâmica; Sinterização; Mechanical Engineering; Rice; Pottery; Sintering; CNPQ::ENGENHARIAS